INTERPRETASI MAKNA SIMBOLIK UNGKAPAN TRADISIONAL SELOKO HUKUM ADAT MELAYU JAMBI - Ade Rahima (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The purpose of this research is to interpretation the symbolic meaning of traditional utterances in seloko Hukum adat Melayu Jambi. This researh is descriptive qualitative by using content analysis method integrated with hermeneutic structural analysis. Hermeneutic structural analysis is aimed at revealing the structure and symbolic meaning of traditional utterances in seloko customary law. The data of this research traditional utterances in seloko customary law which consists of charater education values. The primary data is taken from informants who understand about traditional utterances while the second data is taken from some document and relevant research. The result of the research are. The symbolic meaning which are reflected on seloko text of Melayu basic customary law related with five things, they are: 1) Melayu Jambi customary law through the law of Islam from Holy Quran and Hadist 2) Melayu Jambi customary law through old tradition which is proven having truth or kindness on supporting the society, 3) Melayu Jambi customary law through justice, 4) Melayu Jambi customary law holding fast ot the truth, 5) customary low through partnership. Furthemore, the symbolic meaning of Melayu Jambi customary law related with the forms of felony which are contradicted with customary law and sanction of customary law. The functions of those seloko customary law are devided into 2 (two) parts, they are: (1) as a tool of force and control so that the society obey the customary law (2) as a tool in legalizing regulation, (3) as a tool of learning or character education and children attitude. Key Words: interpretation, symbolic meaning, seloko customary law.